PENGARUH MEREK DAN IKLAN TERHADAP PERILAKU KONSUMEN PADA TOILETRIS RAMAYANA KUPANG - Nire Diah Viriani Ledo; Ronald P.C. Fanggidae; Rolland E. Fanggidae (Universitas Nusa Cendana, 2017)
The purposes of this research is to know and to explain that Brand and Advertisement influencepartially and simultaneously to Consumer Behavior at Toiletris Ramayana Kupang. The researchmethod used is Descriptive Quantitative. Data Analysis Technique using Descriptive Statistic,Classical Assumption Test, Multiple Linear Regression and Hypothesis Test. The results showedthat Brand and Advertisement did not influence partially and simultaneously to ConsumerBehavior.Keywords : Brand, Advertisement, Consumer Behavior